Biofertilizers improve growth rate, nitrate reductase activity, and productivity of shallot (Allium cepa L.) under drought stress - Lena Mardiana; Siswanti, Dwi Umi (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2024)
Shallot (Allium cepa L.) is one of Indonesia's horticultural crops and represents as superior commodity. However, shallots are highly susceptible to drought and require sufficient water for growth. Biofertilizers contain various microbes that provide nutrients and increase the resistance of shallots to drought stress. This study aimed to determine the effect of biofertilizers on the growth rate, nitrate reductase activity, and productivity of shallot plants under drought stress. The research was conducted using a Factorial Completely Randomized Design with two factors. The first factor was the doses of biofertilizer with 0, 10, 15, and 20 L ha-1. The second factor was the drought stress with treatments of 25, 50, 75, and 100% field capacity. Parameters measured included plant height rate, leaf number rate, number of tillers, tuber wet weight, tuber dry weight, and nitrate reductase activity. Data were analyzed by ANOVA using SPSS followed Duncan’s Multiple Range Test (DMRT) at 5% significance level. The results showed that biofertilizer application did no significantly different on the growth rate, but significantly affected the number of tillers, tuber weight, and nitrate reductase activity of shallots under drought stress. The optimum dose of 10 L ha-1 biofertilizer increased the number of tillers (9.33). The optimum dose of 20 L ha-1 biofertilizer increased the growth rate, tuber wet weight (4.46 g), tuber dry weight (0.63 g), and nitrate reductase activity (1.11 µmol NO2- g-1 leaf wet weight h-1 of incubation). It is concluded that biofertilizer application, particularly at 10–20 L ha-1, can improve shallot performance under drought stress and is recommended as a drought mitigation strategy in shallot cultivation.